Measurement and simulation of strain fields around crack tips under mixed-mode fatigue loading (Fracture and Structural Integrity, 2015)
For various configurations examined in a series of fatigue experiments on thin-walled tubes undertension and torsion, the experimental results – crack path, crack growth life, near crack tip deformations, andcrack closure – are measured and compared to the results of some numerical simulations. Partially automatedoptical inspection and the digital image correlation technique were used in the experimental investigation. In thefinite element analyses, an actual geometry of a cracked structure has been modeled. The mechanical materialbehavior has been assumed as linear elastic in a first approach for calculating stress intensity factors. The nonlinearnature of the cyclic deformation has been taken into account by applying a cyclic plasticity model, andplasticity-induced crack closure is captured by a contact formulation.
Keywords: Digital image correlation